Choroid plexus LAT2 and SNAT3 as partners in CSF amino acid homeostasis maintenance - Dolgodilina, Elena (Fluids Barriers CNS, 2020)
BACKGROUND: Cerebrospinal fluid (CSF) is mainly produced by the choroid plexus (CP) located in brain ventricles. Although derived from blood plasma, it is nearly protein-free (~ 250-fold less) and contains about 2–20-fold less free amino acids, with the exception of glutamine (Gln) which is nearly equal. The aim of this study was to determine which amino acid transporters are expressed in mouse CP epithelium in order to gain understanding about how this barrier maintains the observed amino acid concentration gradient. METHODS: Expression of amino acid transporters was assessed in isolated choroid plexuses (CPs) by qRT-PCR followed by localization studies using immunofluorescence with specific antibodies. The impact of LAT2 (Slc7a8) antiporter deletion on CSF amino acids was determined. RESULTS: The purity of isolated choroid plexuses was tested on the mRNA level using specific markers, in particular transthyretin (Ttr) that was enriched 330-fold in CP compared to cerebral tissue. In a first experimental round, 14 out of 32 Slc amino acid transporters tested on the mRNA level by qPCR were selected for further investigation. Out of these, five were considered highly expressed, SNAT1 (Slc38a1), SNAT3 (Slc38a3), LAT2 (Slc7a8), ASC1 (Slc7a10) and SIT1 (Slc6a20b). Three of them were visualized by immunofluorescence: SNAT1 (Slc38a1), a neutral amino acid-Na(+) symporter, found at the blood side basolateral membrane of CP epithelium, while SNAT3 (Slc38a3), an amino acid-Na(+) symporter and H(+) antiporter, as well as LAT2 (Slc7a8), a neutral amino acid antiporter, were localized at the CSF-facing luminal membrane. In a LAT2 knock-out mouse model, CSF Gln was unchanged, whereas other amino acids normally 2–20-fold lower than in plasma, were increased, in particular the LAT2 uptake substrates leucine (Leu), valine (Val) and tryptophan (Trp) and some other amino acids such as glutamate (Glu), glycine (Gly) and proline (Pro). CONCLUSION: These results suggest that Gln is actively transported by SNAT1 from the blood into CP epithelial cells and then released luminally into CSF via SNAT3 and LAT2. Its efflux via LAT2 may drive the reuptake from the CSF of essential amino acid substrates of this antiporter and thereby participates to maintaining the amino acid gradient between plasma and CSF.